PERAN GURU DALAM MENANAMKAN KARAKTER DISIPLIN PADA SISWAKELAS IV MELALUI KEGIATAN PEMBELAJARAN DI SDN KARAWACI BARU 6 - Rita Novia Elviana; M. Hosnan; Suparno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Discipline is one of the keys to success. Discipline is not only owned by students, but all jobs also contain discipline to show that the values of obedience and order are under the applicable norms and rules. Teachers also play a crucial role in solving the lack of discipline among students since students spend much time at school with the teachers, primarily the class teachers. This study aimed to determine how teachers instilled discipline for grade IV students through learning activities. The method used in this research was a descriptive qualitative method. The data collection techniques used were interview, observation, and documentation techniques. This study indicated that the teachers of SDN Karawaci Baru 6 cultivated disciplinary character in grade IV students and knew how to achieve subject characteristics through learning activities